Study of Molecular Interaction in Aqueous KCl at Different Temperatures - Praharaj, M. K. (Journal of Scientific Research, 2021)
Ultrasonic velocity, density, viscosity, and electrical conductivity have been measured for an aqueous solution of KCl at different concentrations and temperatures, the frequency is maintained at a constant value. Using the above experimental data, parameters such as Rao's constant, Wada's constant, solvation number, and surface tension were calculated and the molecular interactions between molecules of KCl and water at different temperatures was studied. Using Walden's plot, the ionicity of the solution was also studied.